PENERAPAN JUST IN TIME DAN DAYA SAING TERHADAP KINERJA UMKM TENUN SUTERA DI KABUPATEN WAJO - Edy Jumady (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to examine and analyze the effect of just in time on the performance of MSMEs. The next objective is to test and analyze the effect of competitiveness on the performance of silk weaving SMEs in Wajo Regency. The design of this study uses an explanatory research approach with data collection carried out in one stage (one short study) through a questionnaire. The number of respondents was 65 respondents at weaving silk SMEs in Wajo Regency. Data analysis method used in hypothesis testing is multiple linear regression. The results of the study provide evidence that (1) just in time has no significant effect on MSME performance, (2) competitiveness influences MSME performance, and (3) just in time and competitiveness simultaneously has positive and significant effect on MSME performance of silk weaving in Wajo Regency.